Performance Appraisal Methods: Essential in Promoting Student Learning - Kapur, Dr. Radhika (International Journal of Management and Humanities, 2024)
In educational institutions of all levels, the educators are required to be well-informed in terms of the factor, whether the students are acquiring an efficient understanding of academic subjects or lesson plans or are overwhelmed by any types of setbacks. Furthermore, they also identify whether they are putting into operation various types of teaching-learning methods and materials in an appropriate manner or there is a need to bring about improvements. Hence, in all grade levels, different types of performance appraisal methods are to be put into operation. These are on the basis of academic subjects and lesson plans. Hence, in order to enhance their participation and achieve good grades, students need to acquire an efficient understanding of different types of academic subjects and lesson plans. The implementation of various types of performance appraisal methods is regarded to be of utmost significance in order to impart information among students in terms of various types of academic subjects and lesson plans. The educators need to ensure, they impart information among students in terms of these in an adequate manner. In other words, students need to be given sufficient amount of time, so they can be well-prepared. Furthermore, it is necessary for students to inculcate the traits of morality, ethics, diligence and conscientiousness. Therefore, performance appraisal methods are essential in promoting student learning. The main concepts that are taken into account in this research paper are, understanding the meaning and significance of performance appraisal methods, understanding performance appraisal methods and advantages of performance appraisal methods.